Saksi Kerajaan Allah: Menguak Strategi Misi Nabi Yeremia Dan Relevansinya Bagi Pelayanan Misi Masa Kini - Adilang, Ryanto; Pananggung, Rifke Alfione (Program Studi Misiologi dan Komunikasi Kristen, 2024)
This article examines the mission strategy of the Prophet Jeremiah in the context of the significant challenges faced by the nation of Israel. Known as the